Im Auge der Physischen Geographie. Vom Blicken und Sehen - Zahnen, Barbara (ERDKUNDE, 2006)
This essay contributes to the theoretical foundation of the question of the significance of the visual in Physical Geography (and other earth sciences). The background of the considerations - while critically including poststructuralistic positions - is generated by hermeneutic-phenomenological approaches from philosophy and the visual arts, which illuminate the how rather than the what of seeing. By critically discussing prevalent conceptions of the function of the visual sense in geographical field work or in the usage of visual materials, different ways of seeing are addressed. This is also done in the face of the question of the respective consequences for the research dynamics of geography and its scientific ambition. Within an ontological scope, the author's considerations result in a conception of what physiogeographical seeing is in a narrower sense.